Improving tensile and flexural properties of SiO2-epoxy polymer nanocomposite. (2018) - Kumar Singh, Sushil; Kumar, Abhishek; Jain, Anuj
Abstract: This study compares the tensile and flexural properties of SiO2 /epoxy polymer nanocomposites. Dispersion of SiO2 nanoparticles in the epoxy polymer was achieved by ultrasonication. SiO2 /epoxy nanocomposites contain varying amount of nano size silicon dioxide (SiO2 ) up to 8 wt.%. The tensile test and three-point bending flexural test were performed to obtain the tensile strength and the flexural properties of nanocomposites respectively. The investigated properties of SiO2 /epoxy nanocomposites increases with the increasing nanoparticles dispersion up to 4 wt.% SiO2 nanoparticles and deterioration in the mechanical properties is realized above 4 wt.%. This may be due to the significant increase in agglomeration and settlement of the SiO2 nanoparticles during the long curing time. The tensile strength increases by 30.57 %, flexural strength by 17 % and flexural modulus by 76 % for 4 wt. % dispersion of SiO2 .